Effect of electrodeposition duration on the morphological and structural modification of the flower-like nanostructured ZnO. (October 2015) - Ait Ahmed, N.; Hammache, H.; Makhloufi, L.; Eyraud, M.; Sam, S.; Keffous, A.; Gabouze, N.
Abstract: Flower-like morphology of ZnO thin films were successfully electrodeposited via a one-step route only by changing electrodeposition duration and potential at a fixed concentration on n-Si (100) in 78.10 −4  M Zn (NO3 )2, 6H2 O and 0.1 M KNO3 solution at 70 °C without using any catalyst, additives or seed layer. The as electrodeposited products were characterized by X-ray diffraction, scanning electronic microscopy and photoluminescence. The effects of the electrodeposition potential and duration on the morphology, structure and photoluminescence properties were studied. The results show that the product morphology changes with a change in the applied voltage and electrodeposition duration. Well defined shape of flower-like ZnO morphology was generated under the limited conditions of −1.2 V for 60 min, with (002) preferred orientation. Strong UV emission is obtained in the case of ZnO flower like morphology electrodeposited at −1.2 V for 60 min. The band-gap energy value of ZnO flower-like, determined from optical reflectance spectra, is 3.37 eV. Highlights: ZnO thin films were electrodeposited on n-Si (100) in zinc nitrate at 70 °C. The effects of the electrodeposition potential and duration were studied. Highly c -axis oriented and flower like morphology was obtained at −1.2 V for 60 min. Strong UV photoluminescence is obtained for ZnO electrodeposited at −1.2 V for 60 min. The band gap energy value of ZnO flower-like morphology is 3.37 eV.